MODELING FORECASTING THE DEVELOPMENT OF THE AGRO-INDUSTRIAL COMPLEX (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article discusses the issues of determining the volume of demand, production, distribution, and consumption of agricultural products, taking into account the specifics of the organization of the processing industry of local raw materials. Based on this consideration, the article proposes a system of tasks and a model for the functioning of the modern agro-industrial complex, describes its functional structure, and establishes the relationship between its main elements.
Keywords: Structure, territory, agro-industrial complex, demand, population.